Prevalence and correlates of cognitive impairment in kidney transplant patients using the demtect—results of a ktx360 substudy - Nöhre, Mariel; Bauer-Hohmann, Maximilian; Klewitz, Felix; Tun, Eva Marie Kyaw Tha; Tegtbur, Uwe; Pape, Lars; Schiffer, Lena; de Zwaan, Martina; Schiffer, Mario (Frontiers in Psychiatry, 2019)
Cognitive impairment in kidney transplantation (KTx) patients is associated with allograft survival and mortality. However, the prevalence of cognitive impairment after KTx is still understudied. Thus, we aimed to assess the prevalence of cognitive impairment in KTx patients and to identify sociodemographic, medical, donation-specific, and psychological variables associated with cognitive impairment. In this cross-sectional two-center study, 583 KTx patients participated in a structured post-transplant care program. The DemTect was used to assess cognition, and cognitive impairment was defined as a score of < 13. Mean age was 52.11 years, 59% were male, 27.4% had ≥12 years of school attendance, and 85.9% had hypertension. The prevalence of cognitive impairment was 15.6%. Cognitive impairment was significantly associated with higher age, male sex, lower educational level, subjective perception of cognitive decline, higher rates of hypertension, lower kidney functioning, and obesity (BMI > 30 kg/m2). Using logistic regression analysis, all variables except age remained significant. Our results suggest that cognitive impairment affects a significant number of patients after KTx. Transplant centers may consider screening for cognitive impairment using objective tests, especially in patients with a high-risk profile. Furthermore, studies with longitudinal designs are required in order to assess moderators and mediators for cognitive trajectories.
CRIS-Team Scopus Importer:2019-11-26
Keywords: cognitive functioning; Cognitive impairment; DemTect; Kidney transplantation; Renal transplantation